Cryopreservation of whole bovine ovaries: comparisons of different thawing protocols. (September 2016) - Gao, Hai-Hua; Li, Zong-Peng; Wang, Hong-Ping; Zhang, Li-Feng; Zhang, Jian-Min
Abstract: Objective: The aim of this study was to perform a comparative investigation of several different thawing protocols and to determine an appropriate protocol for thawing whole bovine frozen ovaries. Study design: Bovine ovaries were slowly frozen and then thawed by applying different protocols. Ultrastructural change, follicle viability, and the hormone levels of culture supernatant were measured. Results: The percentage of morphologically normal primordial follicles and the hormone levels of culture supernatant in group D (two-step, thawing in water at 39 °C) were significantly higher than those in any other group. Moreover, the ultrastructural alteration of oocyte in group D (two-step, thawing in water at 39 °C) was slighter than those in any other group. Conclusions: The two-step protocol involving short-term exposure to water at a moderately high temperature (39 °C) proved to be a suitable for thawing bovine whole ovaries.